Family Continuity and Change : Contemporary European Perspectives - Česnuitytė, Vida; Lück, Detlev; D. Widmer, Eric (Palgrave Macmillan Studies in Family and Intimate Life, 2017)
This volume provides readers with recent sociological approaches to family understanding, theorising and practices within the context of continuities and change, both across generations and during individual life courses. The contributors uniquely investigate the friction between persisting family needs and changing circumstances, between holding on to traditional family norms and adapting to fast-changing demands. Authors from nine countries develop and apply innovative theoretical and methodological approaches for a more differentiated description of European family lives at the beginning of the 21st century, and show that family sociology has achieved significant commonalities across national borders in Europe, thus helping our understanding of complex family realities. The book will be essential reading for students and scholars with an interest in family and intimate life, family sociology and policy, sociology and gender studies. .